Chemical looping technology for energy and chemical production. Issue 2 (21st April 2015) - Bayham, Samuel C.; Tong, Andrew; Kathe, Mandar; Fan, Liang‐Shih
Abstract : Chemical looping has been considered as a promising technology for CO2 capture and for producing electricity and/or chemicals from various carbonaceous feedstocks. This article provides an overview of chemical looping processes, their potential process configurations, and applications for power and chemical production. The designs and results of various demonstration units are discussed in relation to parameters required for commercialization. Furthermore, the barriers to commercialization of a chemical looping plant for power or syngas production are illustrated. WIREs Energy Environ 2016, 5:216–241. doi: 10.1002/wene.173 This article is categorized under: Fossil Fuels > Science and Materials Energy Research & Innovation > Science and Materials Abstract :